TRANSFORMATIONAL LEADERSHIP SYSTEM OF PONDOK PESANTREN IN JAMBI CITY - Sumarto Sumarto (Yayasan Literasi Kita Indonesia, 2021)
The problems faced in Islamic boarding schools, transformative leadership patterns are one of the choices for Islamic boarding school leaders to lead and develop quality Islamic boarding schools. Transformative leadership has an emphasis on clear vision and mission statements, effective use of communication, intellectual stimulation, and personal attention to individual problems of members of the organization. The strategy carried out by Pondok Pesantren Sa'adatuddaren Jambi is the ability to set the direction that is the goal, define and implement a strategic plan to achieve the goal or mission, build a vision, build a common vision, translate the vision and mission into action, develop commitment to work performance, and implement the strategy in institutional operations. The research methodology used in this paper is descriptive qualitative, with data collection techniques using interviews, observation and documentation. Technique of data validity with data triangulation. Data analysis using Miles and Huberman.